Strategic Objectives and Control: Optimizing Strategic Success in the Hospitality Setting through Transformational Leadership - ALHARBI, Ibrahim Bader A. (Journal of Environmental Management and Tourism, 2024)
The aim of the study is to assess the impact of strategic and control objectives on strategic success. Furthermore, it seeks to examine how transformational leadership affects the relationship between goal implementation/commitment and strategic success. Using a quantitative approach, the study collects data through convenience sampling. It is particularly relevant in the hospitality industry in Saudi Arabia. The 378 collected responses are analyzed using partial least squares structural equation modeling technique. The findings confirm all hypotheses of the study except the expected role of transformational leadership in mediating the link between implementation goals and strategic success. The study confirms that strategic and strategic objectives have a significant and positive impact on strategic success. Furthermore, transformational leadership is known to play a facilitating role in the relationship between strategic management and strategic success. This study provides valuable insights and recommendations for practitioners and scholars in the hotel industry in Saudi Arabia.